ANXIETY, DEPRESSION AND STRESS AMONG NURSING PROFESSIONALS AGAINST THE CORONAVIRUS PANDEMIC - Appel, Ana Paula (2022)
Objective: to analyze the sociodemographic and work profile of nursing professionals working in the COVID-19 inpatient unit, who presented, concomitantly, anxiety, depression and stress. Method: a descriptive, cross-sectional study carried out from May to July 2020, via an electronic form, containing a sociodemographic and labor characterization instrument, as well as a scale to assess anxiety, depression and stress - Depression Anxiety and Stress Scale-21. Descriptive and inferential analysis were applied. Results: Mean anxiety was 19.5; 20.0 for depression; and 26.2 for stress. A high correlation was observed between the depression and anxiety subscales (p=0.004). Final considerations: The professionals presented high levels of anxiety, depression and stress. Independent variables with statistically significant values ​​that could clarify the factors associated with anxiety, depression and stress among nursing professionals were not identified. It was possible to observe a statistically significant correlation between the depression and anxiety subscales.